(3GdOjf h GdSjGSI aj GdhdGjGJ GdeJMOI (B/s - (3eGjcd,chQHJ,LhdjG ejJTd,chQHJ s; (3YUGe(B,(3aGjR (B;(3fGgO(B,(3hUais ((3GdbGgQI (B:s (3ecJHI GdTQhb ,s, 2002)
(3jSJYQV gPG GdcJGH GdCcGOjej JaGYd GdOjf h GdSjGSI aj GdhdGjGJ GdeJMOI GdCeQjcjI efP GdgLQI h HfGA GdeSJYeQGJ aj GdbQf GdSGHY YTQ h MJi fgGjI GdbQf GdYTQjf (B.(3Jdc GdSjGSI GdJj JDKQ aj GdYGde cdg HeG aj Pdc eUQ h GdTQb GdChSW s
Keywords: (3GdOjfs; (3GdSjGSIs; (3GdhdGjGJ GdeJMOI s